Influenza vaccination uptake and factors influencing vaccination decision among patients with chronic kidney or liver disease. - Michael Eder; Haris Omic; Jana Gorges; Florian Badt; Zeljko Kikic; Marcus D Saemann; Allison Tong; David Bauer; Georg Semmler; Thomas Reiberger; Heimo Lagler; Bernhard Scheiner (PLoS ONE)
Introduction Seasonal influenza is a major global health problem causing substantial morbidity and health care costs. Yet, in many countries, the rates of influenza vaccination remain low. Chronic kidney or liver diseases (CKLD) predispose patients to severe influenza infections, but data on vaccination acceptance and status is limited in this risk population. We investigated the influenza vaccination awareness considering sociodemographic factors in CKLD patients. Patients and methods This cross-sectional, questionnaire-based study recruited CKLD patients managed at three Viennese tertiary care centers between July and October 2020. CKLD was defined as chronic kidney- (all stages) or compensated/decompensated liver disease, including kidney/liver transplant recipients. Questionnaires assessed sociodemographic and transplant- associated parameters, patients vaccination status and the individuals self-perceived risks of infection and associated complications. Results In total 516 patients (38.1% female, mean age 56.4 years) were included. 43.9% of patients declared their willingness to be vaccinated in the winter season 2020/2021, compared to 25.4% in 2019/2020 and 27.3% in 2016-2018. Vaccination uptake was associated with the self-perceived risks of infection (OR: 2.8 (95%CI: 1.8-4.5), p<0.001) and associated complications (OR: 3.8 (95%CI: 2.3-6.3), p<0.001) as well as with previously received influenza vaccination (2019/2020: OR 17.1 (95%CI: 9.5-30.7), p<0.001; season 2016-2018: OR 8.9 (95%CI: 5.5-14.5), p<0.001). Most frequent reasons for not planning vaccination were fear of a) graft injury (33.3%), b) complications after vaccination (32.4%) and c) vaccine inefficiency (15.0%). Conclusion While influenza vaccination willingness in patients with CKLD is increasing in the 2020/2021 season, vaccination rates may still remain <50%. Novel co-operations with primary health care, active vaccination surveillance and financial reimbursement may substantially improve vaccination rates in high-risk CKLD patients.